EVALUASI KINERJA ALAT ROTARY KILN DITINJAU DARI EFISIENSI TERMAL DAN AIR FUEL RATIO (AFR) DI PBR II PT. SEMEN BATURAJA Tbk - Niko, Niko; Abimanyu, Abraham; Safaruddin, Safaruddin (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
Clinker is an artificial rock produced from kiln feed or rawmeal through a process that occurs in a rotary kiln with a temperature of around 1450°C. In the heating process in the rotary kiln, physical reactions and chemical reactions occur simultaneously. The methodology used to complete this article consists of several stages including the following: Taking actual condition data from the Central Control Room (CCR) and composition data from the Quality Control (QC) laboratory. From the results of the performance evaluation, the thermal efficiency of the rotary kiln is still classified as good with an average of 74.05% where the good efficiency ranges from 71%-84%. This value indicates that the performance of the rotary kiln is still fairly good when viewed from the actual calculated thermal efficiency. Regular checking, maintenance and repair is an increase in the performance of rotary kiln equipment so that the obstacles experienced can be reduced. he decrease and increase in AFR value is also influenced by the size of the feed flow rate that enters the combustion process.